The effect of austenitic interface layer on microstructure of AISI 420 martensitic stainless steel joined by keyhole PTA welding process - Kurt, Bulent; Orhan, Nuri; Somunkiran, Ilyas; Kaya, Mehmet (Elsevier Sci Ltd, 2009)
In this study, a martensitic stainless steel plate of 10 mm thick was welded by keyhole plasma transfer arc (PTA) welding technique both itself and using austenitic stainless steel plate of 2 mm thick in interface. So, penetration depth, microstructure, mechanical behavior and interface layer effects of keyhole plasma welding were investigated. After keyhole plasma welding, microstructural analysis including metallographic examination, and notch impact strength tests were performed. From the results, it was seen that with this technique can be obtained penetration depth of 8 mm without any pretreatment of welding. Also, austenitic stainless steel interface layer was raised impact strength of welding. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Plasma welding; Keyhole; Martensitic stainless steel; Austenitic interface layer